2009
DOI: 10.2176/nmc.49.484
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multi-staged Surgery and Adjuvant Chemotherapy for Successful Treatment of Atypical Choroid Plexus Papilloma in an Infant -Case Report-

Abstract: A 12-month-old girl presented with a rare atypical choroid plexus papilloma manifesting as conscious disturbance and vomiting. Magnetic resonance (MR) imaging revealed a well-delineated 5 × 6-cm lobulate mass in the right lateral ventricle. Only partial removal of the tumor was performed because of excessive intraoperative hemorrhage at the first surgery. The histological diagnosis was atypical choroid plexus papilloma. To control the intraoperative hemorrhage, embolization of the feeding artery was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In their report on an atypical choroid plexus papilloma, Takahashi and colleagues suggested that the exceptionally vascular nature of the tumor described ultimately led to their decision to stage surgery. 14 Similar reports in the literature describe instances in which signi cant vascularity of intra-axial tumors has led to the decision to pursue a staged surgery intraoperatively. Kumabe et al reported a case in which multi-stage surgery separating debulking and subcortical mapping was used in a case of anaplastic astrocytoma, and gross total resection without neurological de cit was achieved.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In their report on an atypical choroid plexus papilloma, Takahashi and colleagues suggested that the exceptionally vascular nature of the tumor described ultimately led to their decision to stage surgery. 14 Similar reports in the literature describe instances in which signi cant vascularity of intra-axial tumors has led to the decision to pursue a staged surgery intraoperatively. Kumabe et al reported a case in which multi-stage surgery separating debulking and subcortical mapping was used in a case of anaplastic astrocytoma, and gross total resection without neurological de cit was achieved.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, 7 papers were selected (Table 1) and included for further analysis. [14][15][16][17][18][19][20][21][22][23] Types of papers included 3 case series, 3 case reports, and 1 technical note (Table 1). The study publication dates ranged from 1998-2019.…”
Section: Database Searchmentioning
confidence: 99%
“…As stated earlier, there is no paper investigating treatment options for atypical CPP in infants. Authors in one of the case reports have in fact suggested that atypical CPP should be considered as CPC and treated the patient with chemotherapy [32]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of neoadjuvant chemotherapy in CPC has been reported as an approach that leads to a decrease in blood loss in patients undergoing surgery [ 7 ]. Preoperative embolization, albeit limited to a small number of patients, has been attempted since the end of the 90s, with encouraging results in terms of reducing blood loss, which, in turn, reduces morbidity and mortality and increases the likelihood of total resection ( Supplementary Table S1 ) [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, the small and tortuous vasculature of small children, and the typical involvement of eloquent arteries, represent a significant hindrance.…”
Section: Introductionmentioning
confidence: 99%